Exiting from the crisis: towards a model of more equitable and sustainable growth. Report of a trade union task force (Brussels, 2011)
"The global economy is still struggling to emerge from the worst financial crisis and global recession since the Second World War. In this context, TUAC, ETUI, GURN and ITUC created a Task Force to define the parameters of a new growth model. This publication which is the initial result of its work, takes up the challenge of developing progressive alternatives to the failed neo-liberal model that has dominated economic policy for over three decades. It consists of contributions by more than 30 authors, all with links to the global labour movement, and a preface by Nobel Prize laureate Joseph Stiglitz.